Firm-level and local labor market effects of a large credit shock: Evidence from Brazil - Carlos Henrique Corseuil; Luciano Machado; Fabio Roitman; Gabriel Ulyssea (Instituto de Pesquisa Econômica Aplicada (IPEA), 2023)
A common explanation for the poor performance of entrepreneurs in developing economies is their inability to obtain credit to expand their scale of operation. This paper assesses the aggregate impacts of the Cart\~ao BNDES, a credit line targeted at small and medium enterprises (SMEs) in Brazil, to investigate the role of credit constraints on SMEs performance. We use a major expansion of credit supply within the line to estimate causal effects of credit supply on firm size distribution, entry and exit, and employment. By exploiting the fact that firms can only use the available credit with suppliers that are registered in the credit line's system, we construct a variable that capture a credit supply expansion that varies exogenously across regions. We use an instrumental variable estimator that exploits differential access to the line and the expansion of suppliers to recover these causal effects. Our main result points that a 1% increase in the Brazilian Development Bank (Banco Nacional de Desenvolvimento Econômico e Social - BNDES) card loans has a positive effect on average local formal employment between 6.7% and 10.3%. This increase in employment is driven by the increase in the average size of firms, specially by the average size of new entrant firms. These are relevant results as they suggest that the type of credit provided by BNDES card foster the dynamics of local labor markets, increasing the entrance of new firms, which are pointed as the group most affected by credit constrains.
Keywords: H81; J08; 330; credit; employment; local labor market